2022
DOI: 10.1097/fjc.0000000000001178
|View full text |Cite
|
Sign up to set email alerts
|

Role of Circadian Rhythm and Impact of Circadian Rhythm Disturbance on the Metabolism and Disease

Abstract: :Molecular circadian clocks exist in almost all cells of the organism and operate for approximately 24 hours, maintain the normal physiological and behavioral body processes, and regulate metabolism of many cells related to a variety of disease states. Circadian rhythms regulate metabolism, mainly including neurotransmitters, hormones, amino acids, and lipids. Circadian misalignment is related to metabolic syndromes, such as obesity, diabetes, and hypertension, which have reached an alarming level in modern so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 130 publications
(206 reference statements)
0
8
0
Order By: Relevance
“…For instance, circadian misalignment and disruptions in circadian rhythms have been associated with an increased risk of various diseases, including cancer (20)(21)(22)(23). The maintenance of normal levels of PER1 and BMAL1 is crucial for proper functioning of the circadian rhythm, and disruptions in their expression can have significant implications for human health (24). Mrtadichol@100 ng was used to maintain normal levels.functioning of the circadian rhythm, and disruptions in their expression can have significant implications for human health ().…”
Section: Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, circadian misalignment and disruptions in circadian rhythms have been associated with an increased risk of various diseases, including cancer (20)(21)(22)(23). The maintenance of normal levels of PER1 and BMAL1 is crucial for proper functioning of the circadian rhythm, and disruptions in their expression can have significant implications for human health (24). Mrtadichol@100 ng was used to maintain normal levels.functioning of the circadian rhythm, and disruptions in their expression can have significant implications for human health ().…”
Section: Interactionsmentioning
confidence: 99%
“…Circadian rhythms are intrinsic 24-hour cycles that are fundamental to physiological and behavioral processes in almost all organisms, including humans. These rhythms are driven by a biological clock, a complex orchestration of genes and proteins that regulate the timing of various bodily functions (1,2).…”
Section: Introduction;mentioning
confidence: 99%
“…Overexpression of clock components can also prevent the generation of deleterious vascular phenotypes (Qin and Deng, 2015). Circadian rhythms also regulate metabolism and digestion primarily via through this feedback loop (Zhong et al, 2018;Segers and Depoortere, 2021), which controls and drives metabolism, mainly including neurotransmitters, hormones, amino acids, and lipids (Han et al, 2022). Meanwhile, the circadian rhythm and metabolism interact with each other to maintain normal physiological activities (Reinke and Asher, 2019;Takahashi, 2019;Sinturel et al, 2020).…”
Section: B C a Figurementioning
confidence: 99%
“…Recent study reported that circadian rhythms is a controllable therapeutic strategy that can improve obesity [8,9]. The circadian rhythms are governed by in the suprachiasmatic nucleus, which is in the hypothalamus of the brain [10].…”
Section: Introductionmentioning
confidence: 99%